Student visual learning style activities in javanese script writing learning - Iryani, Evi (Aksara: Jurnal Bahasa dan Sastra, 2023)
The learning activities undertaken by students are essential to be known as the basis for teachers to determine suitable teaching methods and media according to the characteristics of the students. The implication of this research is that teachers can create effective learning experiences by aligning teaching methods and media with the visual learning preferences of students. The research subjects were eighth-grade students at SMP Darussalam Bergas who have a visual learning style. The data for the research included all activities of students with a visual learning style. Data analysis was conducted using Miles and Huberman's data analysis model, which includes data reduction, data presentation, and drawing conclusions. The data analysis results revealed that the characteristics of visual learning style predominantly dominated the students' learning preferences. The activities of visual learners include the following: they find it easier to comprehend what they see rather than what they hear, pay attention to PowerPoint presentations, are more organized and neat, prefer reading to being read to, are meticulous and detail-oriented, have good spelling skills, tend to doodle without specific meaning, are not easily distracted by noise but may be disrupted if the visual display is unclear, visual learners tend to copy everything written by the teacher on the chalkboard, and they prefer to sit near the front of the classroom to have a clear view. Keywords: learning activities, Javanese script, visual learning style